Beginning Node.js - Syed, Basarat (Apress : Imprint: Apress, 2014)
Beginning Node.js is your step-by-step guide to learning all the aspects of creating maintainable Node.js applications. You will see how Node.js is focused on creating high-performing, highly-scalable websites, and how easy it is to get started. Many front-end devs regularly work with HTML, CSS, PHP, even WordPress, but haven't yet got started with Node.js. This book explains everything for you from a beginner level, enabling you to start using Node.js in your projects right away. Using this book you will learn important Node.js concepts for server-side programming. You will begin with an easy-to-follow pure JavaScript primer, which you can skip if you're confident of your JS skills. You'll then delve into Node.js concepts such as streams and events, and the technology involved in building full-stack Node.js applications. You'll also learn how to test your Node.js code, and deploy your Node.js applications on the internet. Node.js is a great and simple platform to work with. It is lightweight, easy to deploy and manage. You will see how using Node.js can be a fun and rewarding experience - start today with Beginning Node.js.